2006
DOI: 10.1016/j.devcel.2006.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Signaling Mediates Self-Organizing Tissue Migration in the Zebrafish Lateral Line

Abstract: The shape of most complex organ systems arises from the directed migration of cohesive groups of cells. Here, we dissect the role of the chemokine guidance receptor Cxcr4b in regulating the collective migration of one such cohesive tissue, the zebrafish lateral line primordium. Using in vivo imaging, we show that the shape and organization of the primordium is surprisingly labile, and that internal cell movements are uncoordinated in embryos with reduced Cxcr4b signaling. Genetic mosaic experiments reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
546
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 479 publications
(574 citation statements)
references
References 28 publications
20
546
0
1
Order By: Relevance
“…2J, arrows), suggesting that SDF1/CXCR4 and Wnt/LEF1 signaling redundantly repress this gene in the leading cells. We cannot rule out, however, the alternative possibility that cxcr7b expressing cells are transiently present in the leading region due to abnormal cell movement within the primordium (Haas and Gilmour, 2006). Contrary to cxcr4b, cxcr7b is not expressed at all at the early stage where cxcr4b is ubiquitously expressed (Fig.…”
Section: Developmental Dynamicsmentioning
confidence: 92%
See 4 more Smart Citations
“…2J, arrows), suggesting that SDF1/CXCR4 and Wnt/LEF1 signaling redundantly repress this gene in the leading cells. We cannot rule out, however, the alternative possibility that cxcr7b expressing cells are transiently present in the leading region due to abnormal cell movement within the primordium (Haas and Gilmour, 2006). Contrary to cxcr4b, cxcr7b is not expressed at all at the early stage where cxcr4b is ubiquitously expressed (Fig.…”
Section: Developmental Dynamicsmentioning
confidence: 92%
“…We therefore repeated the experiment in 26 hpf embryos that were doubly transgenic for cxcr4b:rfp and for cldnb:gfp, where all cells of the PLL system express a membranebound green fluorescent protein (GFP; Haas and Gilmour, 2006). We observed that the level of red fluorescence at 26 hpf was reduced by 50% in morphant vs. control embryos (Figs.…”
Section: Lef1 Is Required For Cell Proliferation In the Pll Placodementioning
confidence: 99%
See 3 more Smart Citations